AI in Translation: How to Use it Effectively - V. V. Sdobnikov (Научный диалог, 2025)
The article considers the problem of the impact of the procedures of using artificial intelligence systems on the translators’ professional mindset. The aim of the article is to determine the conditions under which the use of machine translation systems, in particular, based on the use of artificial intelligence, allows to effectively solve the tasks of professional translation activity. The main research method used is the analysis of empirical data obtained by observing the professional activities of experienced and novice translators. This analysis shows that translators often do not take into account that the product created by artificial intelligence is not a text in the traditional meaning of the word, but can only be considered a textoid. Within the framework of interaction with the artificial intelligence system, translators forget about the need to create a true text, i.e. a communicative and structural-semantic unity, do not perceive the intratextual logical links lost in the textoid produced by the artificial intelligence, and — most importantly — forget about the purpose of the translation product, the form and content of which should meet the expectations of the intended target text recipient in a given communicative situation. The article concludes that to ensure the effective use of artificial intelligence systems, the translator must constantly keep in mind the inherent limitations of such systems and must not perceive himself as an appendage to such a system; all his efforts must be directed towards the production of a text that satisfies the needs of the consumer.